Telemedicine for Eating Disorders: A Brief Report of a Italian Project - Savarese, Giulia; Carpinelli, Luna; Padovano, Maria Rosaria; Pecoraro, Nadia; Fasano, Oreste; Mollo, Monica; Giovanni, Claudio Di; Politi, Martino (Advances in Social Sciences Research Journal, 2020)
The objectives of the present work are the research and development of a Telemedicine system for therapy and enhanced monitoring of Eating disorders (ED). To this end, useful tools have been developed both for patients and caregivers and for operators: a) a mobile application for medical and psychological updates on the status of patients and through which it is possible to access psychological counselling services for family caregivers; and b) virtual and immersive reality viewers for the therapy of ED patients with social anxiety.